Pseudospiropes ehretiae sp nov from Uttar Pradesh - KAMAL, R.K. VERMA* and (Indian Phytopathology, 2002)
P. ehretiae sp. nov. collected from living leaves of Ehretia laevis at Baharaich, Uttar Pradesh, India, is described and illustrated.